PENERAPAN METODE WEIGHTED AVERAGE PADA SISTEM KEPUASAN PENGUNJUNG TERHADAP KUALITAS PELAYANAN DI PENGINAPAN RUMAH NAKATA - Rahma Sarita Khairunnissa; Zein Vitadiar, Tanhella; Muhammad Fatkhur Rizal; Setyo Permadi, Ginanjar (Fakultas Teknologi Informasi, 2024)
The visitor satisfaction information system for service quality is an innovative solution to measure andimprove service quality in a public service. One of them is at the Nakata house inn, which provideslodging facilities for its visitors. However, with adequate facilities, Nakata's house still has one of itsshortcomings in the service system that makes communication between employees and visitors miss andthe limitations of promotions that are carried out so that it affects the satisfaction and interest of visitors.This research uses the weighted average method which aims to develop an information system inanalyzing and evaluating the level of visitor satisfaction with the quality of service. The weighted averagemethod is used to give weight to various aspects of the service that are assessed by visitors. So that theevaluation becomes accurate and detailed. This research involves collecting data from visitors throughquestionnaires and interviews, as well as data management using the weighted average method analysis.The results of this study show that the response from the response to the quality of Nakata house lodgingservices is included in a good category, because they get a score of 78 and the specification of the highestservice type in the employee responsibility category with a value of 3.5, while with the lowest valuespecification is found in the snack category with a value of 2.1. it is expected to provide concreterecommendations for lodging service providers in improving the quality of service based on the prioritydetermined by visitors. The visitor satisfaction information system for service quality using the weightedaverage method is expected to be able to make strategic decisions to increase visitor satisfaction andservice quality well and efficiently.Keywords: visitor satisfaction survey, lodging, service, weighted average